IMPROVING STUDENTS’ READING ABILITY BY USING TASK BASED LEARNING OF VII GRADE AT SMP N 2 OGODEIDE - Reza Aprilieah (Jurnal Madako Education, 2018)
The aim of this research is to describe the application of Task Based Learning strategy to improve students’ ability in reading descriptive text. This research was conducted at SMP Negeri 2 Ogodeide from March to April 2017. This research is categorized as a collaborative classroom action research. The researcher worked collaboratively with one English teacher, Mr. Lisman S.Pd in the class. The researcher did two cycles in which each cycle consists of planning, acting, observing, and reflecting. The data were gathered through qualitative and quantitative data. The qualitative data were gained by analyzing observation result, field note, and interview. Then quantitative data were obtained from the students’ reading test. The result of this study show that task based learning is effective in improving students’ reading ability. Researchers conduct II cycles in this study. In cycle I the students’ mean score increased from 48% (preliminary test result) to 68% (final result of cycle I test). In cycle II, the students’ mean score is 80%. This means that classroom action research is successful. Then, the researcher concludes from this data, that task based learning is appropriate for reading because it makes students more active, participation and student value increase in reading ability. Key Word: Improving, Reading ability, Descriptive text, Task based learning.